Yield Effects of Tissue Culture Bananas in Kenya: Accounting for Selection Bias and the Role of Complementary Inputs - Nassul S. Kabunga; Thomas Dubois; Matin Qaim (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
We analyze yield effects of tissue culture (TC) banana technology in the Kenyan small farm sector, using recent survey data and an endogenous switching regression approach. TC banana plantlets, which are free from pests and diseases, have been introduced in East Africa since the late-1990s. While field experiments show significant yield advantages over traditional banana suckers, a rigorous assessment of impacts in farmers' fields is still outstanding. A comparison of mean yield levels between TC adopters and non-adopters in our sample shows no significant difference. However, we find a negative selection bias, indicating that farmers with lower than average yields are more likely to adopt TC. Controlling for this bias results in a positive and significant TC net yield gain of 7%. We also find that TC technology is more knowledgeintensive and more responsive to irrigation than traditional bananas. Simulations show that improving access to irrigation could lift TC productivity gains to above 20%. The analytical approach developed and applied here may also be useful for the evaluation of other knowledgeintensive package technologies and innovations in perennial crops.
Keywords: 330; Biotechnology; adoption; productivity; impact; endogenous switching regression; Kenya